Exploring Insights and Prospectives of Local Teachers towards Teaching Profession at Community School of Nepal - Baraily, Khagendra (Educational Journal, 2025)
The perception of local teachers within a community plays a pivotal role in shaping educational experiences and outcomes. Local teachers are recognized as regional leaders and engage in community functions besides family work. This study intends to explore the multifaceted nature of community perception and teachers' experience, delving into the factors that influence such perception and their broader implications. A qualitative research method with a phenomenological research design has been adopted for this study. Four community school teachers were purposively selected as research participants from the community school located in Morang district, and in-depth interviews were conducted via semi structured interview guidelines. The interview responses were transcribed verbatim, and thematic analysis techniques were employed to conclude this study. The transcription was coded and organized with profound reading. The global themes were extracted with the intersection of commonalities within the organized codes arrised from the quotation of participants. The findings include that the academic prowess of teachers does not solely influence community perception but also encompasses their interpersonal skills, dedication, and engagement with students and families. Socioeconomic background, cultural values, and prior experience contribute to a community's diverse spectrum of opinions. Understanding this perception is crucial for educational institutions and policymakers as they strive to enhance teaching quality, foster positive community relationships, and create an inclusive and supportive learning environment. The study findings underscore the significance of fostering strong teacher-community rapport and the need for ongoing dialogue to align educational practice with community expectations.